THE EFFECTIVENESS OF THE FLIPPED CLASSROOM STRATEGY IN ENHANCING ACADEMIC COMMUNICATION SKILLS AMONG NINTH GRADE STUDENTS - Mohanad Yousif Khammas; Kareem Ahmed Mohammed Al-Bayati; Sufyan Hasan Ahmed (Journal of Social Science, 2026)
Objective: This study aimed to evaluate the effectiveness of the flipped classroom strategy in developing academic communication skills among preparatory stage students in Kirkuk Governorate. Method: A quasi-experimental design was employed, with experimental and control groups and pre- and post-measurements. The sample comprised 180 students, aged 12-14, from four classes, equally representing both genders. Results: The experimental group exhibited statistically significant improvements in academic communication skills, with mean scores increasing from 45.12 ± 6.35 to 62.88 ± 5.72 (t = 12.47, p = 0.000). Repeated Measures ANOVA revealed significant enhancement in individual skills: oral expression (65.40 ± 6.12), written expression (60.36 ± 5.88), group interaction (63.50 ± 6.00), presentation (61.90 ± 5.90), and scientific discussion (64.20 ± 5.85), all showing significant differences (F = 12.78, p = 0.000). The control group did not exhibit significant changes. Novelty: The study highlights the flipped classroom strategy's impact on fostering a wide range of academic communication skills, confirming its effectiveness and offering support for its application in educational settings, consistent with previous studies.